Women’s reproductive health factors and body adiposity: findings from the UK Biobank - Peters, S.; Huxley, Rachel; Woodward, M. (2015)
Objective: To conduct a comprehensive examination of the association between women’s reproductive health factors and measures of body adiposity in a contemporary Western population. Methods: A cross-sectional analysis of 502 664 individuals from the UK Biobank was conducted. Multivariable linear regression models were used to examine the association of age at menarche, age at first birth, parity and age at menopause with measures of general and central body adiposity, adjusted for age, smoking and socioeconomic status. The association between number of children and body adiposity in men was also assessed. Results: Age at menarche was inversely associated with body mass index (BMI); adjusted mean BMI was 29.0 kg m–2 in women with menarche before the age of 12 years, compared with 26.5 kg m–2 in those who had menarche after 14 years of age. Age at first birth was linearly and inversely associated with BMI: 0.16 kg m–2 lower BMI per year increase in age of first birth. Each additional live birth or child fathered was associated with a 0.22 kg m–2 higher BMI in women and a 0.14 kg m−2 higher BMI in men. There was no evidence for an association between age at menopause and BMI. Corresponding associations for other markers of general or abdominal adiposity were similar to those for BMI. Findings were broadly similar in analyses stratified by age, smoking status, socioeconomic status, ethnic background, and history of diabetes or cardiovascular disease. Conclusions: In women from a contemporary Western population, earlier age at menarche and age at first birth, and higher number of total live births were associated with higher levels of body adiposity. Prospective evaluations of the association between reproductive health factors, adiposity and the onset of cardiometabolic diseases are needed to assess causality, and to explore the mechanisms involved.